Rupture, repair, the loss and re-construction of identity: Seeking support in situations of adolescent-to-parent violence and abuse - Rutter, Nikki (Frontiers in Health Services, 2023)
Family violence is associated with life-long implications including increased vulnerability to poor mental and physical health, and increased risk of repeat victimization. When children or adolescents are the ones instigating the harm, mothers experience the compounding issues of violence, mother-blame, and stigma. In comparison to other forms of family violence, how mothers understand and interpret their experiences of adolescent-to-parent violence and abuse (APVA) is underexplored, particularly in relation to what it means for them at the emotional and individual level, and how this impacts their sense of self, and their mothering and professional identities. This brief research report uses an interpretive phenomenological approach utilising hermeneutics to explore how six mothers made-meaning of their lives and identity when their parenting journey was disrupted by APVA. Help-seeking behaviours were often met with denial, avoidance, and parent-blame from professionals, unless they were familiar with the mother through her professional identity first. Neurodivergences of the adolescents were reported, including mental illness, autism, pathological demand avoidance, and foetal alcohol spectrum disorder. and as no mother reported successful engagement with social care, youth justice, or mental health services when help-seeking, they needed to reimagine their parenting role, or hit crisis, before accessing appropriate support. Mothers could have been supported earlier if critical incidents were identified by services, and support and/or interventions provided earlier, when mothers first engaged in help-seeking behaviours.